(untitled) (Current Problems in Rail Vehicles, 2021)
Based on the computer simulations the potential effect of various systems for reduction of guiding forces in track curves for electric locomotives are compared. From this comparison, the greatest potential is shown by active wheelset steering, which is further examined in the article in terms of detecting the radius of the track curve, control algorithms and sensitivity to variable track parameters and vehicle speed. The proposed system of active wheelset steering is then tested by computer simulations of vehicle run in a real section of a track with a length of 21 km and the results are compared with a vehicle in a conventional arrangement.